Resolution of atrial-ventricular block secondary to Listeria monocytogenes with antimicrobials - Shobayo, Anuoluwapo (IDCases, 2019)
Listeria endocarditis is a rare, but serious disease with high mortality rate. Currently, little is known regarding the optimal treatment modality of Listeria endocarditis in affected individuals. Here, we present the case of a 66-year-old female with history of mitral and aortic replacement with bioprosthetic valve, and hospital course complicated by Listeria monocytogenes infective endocarditis with atrial-ventricular (AV) block. Listeria monocytogenes infection was eradicated by a 6-week antimicrobials course involving ampicillin and gentamicin, culminating in the resolution of AV block. On further investigation, the patient admitted to frequent consumption of salami and provolone cold-cut sandwiches, which based on previous evidence in literature is hypothesized to be the source of infection. Our findings suggest the development of perivalvular abscesses as the cause of the AV block. To our knowledge, this is the first reported case in literature where AV block secondary to listeriosis resolved with treatment solely by antimicrobials. While further research and larger studies are needed to extend our findings, patients with AV block secondary to listeriosis may benefit from optimized management with antimicrobials.